Charles Dickens and Intellectual Disability - Polloway, Edward A.; Smith, J. David; Patton, James R. (Journal of Intellectual Disability - Diagnosis and Treatment, 2015)
Throughout civilization, the power of the word has significantly influenced and shaped societies. The contributions of writers has been substantial and this is certainly true in the field of intellectual disability. The renowned author, Charles Dickens, spoke of the need for appropriate education and treatment for people with these disabilities. He is notable for his early and prophetic vision of their potential for growth. This paper reviews important examples that were included in his novels as well as in other writings on people with intellectual disabilities. The manuscript places his work in an historical perspective, highlights his contributions to the literature of disability advocacy, and references his relevance to the field of intellectual disability.